2004
DOI: 10.1037/0022-3514.87.5.698
|View full text |Cite
|
Sign up to set email alerts
|

Night and Day: Are Siblings as Different in Temperament as Parents Say They Are?

Abstract: Twin studies suggest that parent ratings of temperament exaggerate differences between twins. The present study examined whether such contrast effects also operate for nontwin siblings. The activity level (AL) and shyness of 95 nontwin sibling pairs (ages 3 to 8 years) were assessed via parent ratings and objective measures (actigraph and observer ratings). Siblings showed no resemblance in either parent-rated AL or shyness; however, sibling resemblance for actigraph AL and observer-rated shyness was substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
70
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 50 publications
13
70
4
Order By: Relevance
“…Plomin (1982) suggest that contrast effects are more likely when the items refer to global descriptions of behavior rather than to specific descriptions of behavior. This was confirmed by Saudino et al (2004), who report a tendency for contrast effects to be more pervasive when global ratings were required. The lack of contrast effects in the current study shows that the items of the CBCL are specific enough to prevent parents from comparing the behavior of the twins.…”
Section: Discussionsupporting
confidence: 63%
“…Plomin (1982) suggest that contrast effects are more likely when the items refer to global descriptions of behavior rather than to specific descriptions of behavior. This was confirmed by Saudino et al (2004), who report a tendency for contrast effects to be more pervasive when global ratings were required. The lack of contrast effects in the current study shows that the items of the CBCL are specific enough to prevent parents from comparing the behavior of the twins.…”
Section: Discussionsupporting
confidence: 63%
“…Of note, measurement error is captured by the within-family variance, and we acknowledge the variable internal consistency in our scales. The sole use of maternal reports here may inflate our associations due to rater bias and contrast effects (Saudino, 2004), as well as "perceiver effects" whereby parent characteristics affect their interpretation of child and own behaviors (Manders, Janssens, Cook, De Bruyn, & Scholte, 2009). Previous studies indicate that although parent reports identify less PDT, the PDT reported by mothers is associated at least as strongly with child adjustment as is PDT reported by children (e.g., Coldwell, Pike, & Dunn, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Discrepancies are critical for numerous reasons. First, they are present across measurement methods (De Los Reyes & Kazdin, 2005) and areas of psychological science (e.g., Barrett, 2006;Clancy, McGrath, & Oddson, 2005;Kenny, Albright, Malloy, & Kashy, 1994;Saudino, Wertz, Gagne, & Chawla, 2004). Second, discrepancies pose significant interpretive problems for researchers studying …”
mentioning
confidence: 99%